PENERAPAN MODEL PEMBELAJARAN COOPERTIVE INTEGRATED READING AND COMPOSITION (CIRC) UNTUK MENINGKATKAN HASIL BELAJAR BAHASA INDONESIA DIKELAS IV SDN INPRES 6/84 WALEHUNIAN SAGERAT - Horman, Meisara Leonita; Rindengan, Mersty E; Rawung, Jennej J (Bloom Journal, 2024)
This research aims to improve student learning outcomes in the Indonesian language subject for Class IV Students at SDN Inpres 6/84 Walehunian Sagerat by implementing the Cooperative Integrated Reading and Composition (CIRC) learning model. This type of research is Classroom Action Research. The data collection technique is carried out using observation and test techniques. Based on the problems found in students in class IV of SDN Inpres 6/84 Walehunian Sagerat, out of a total of 19 students, only 8 students got a pass mark or 42%. Meanwhile, 11 students need to improve their learning results or 57%. Therefore, this research was carried out in two cycles, where in the first cycle the student learning outcomes whose scores reached KKM were 13 students and only 73.68% of the 19 students were reached so it was continued in the second cycle, which improved the learning process so that student learning outcomes who achieved KKM 18 out of 19 students, increased to 83.68%. From these results the researcher can conclude that the use of the Cooperative Integrated Reading and Composition (CIRC) learning model can improve the learning outcomes of class I V students at SDN Inpres 6/84 Walehunian Sagerat in the Indonesian language subject